The Establishment of Optimized Management of The Economic Potential of Regional Communities Through BUMDes and UMKM - Herman Yaarozatulo Harefa (International Journal of Regional Innovation, 2021)
This study discusses the innovation of BUMDes and also SMEs in order toimprove the economy and improve community efforts in managing potentialeconomyowned by the area. Of course, this research will explore the problems that occur in BUMDes and UMKM as well as the role of the government and society in realizing a stable and prosperous community economy by implementing innovations that have been made to achieve these goals.This study uses a qualitative method.In this study, data collection was also carried out through searching various sources which were then processed and described in narrative form according to data needs. The population in this study is an area that has made innovations in the field of UMKM and also BUMDES which aims to grow and develop businesses in order to build a prosperous community economy. While the research subjects are in West Java Province with the innovation of the UMKM Outlet System and in Morotai Island Regency with its innovation, namely IT Bumdes. This study shows that local government and community participation in realizing innovations made in order to create a stable and prosperous community economy have succeeded in answering the problems that occurred, especially in West Java and Morotai Island Regency. With the creation of the UMKM Outlet System innovation in West Java and the IT innovation of Bumdes, Morotai Island Regency managed to provide an application system that can accommodate the development needs for the Cooperatives and Small Business Office as well as Small Business actors in the aspect of data and information processing. As well as providing services to the local community by placing prices and services according to market standards that do not cause distortions in the rural economy caused by BUMDes efforts. With the creation of the UMKM Outlet System innovation in West Java and the IT innovation of Bumdes, Morotai Island Regency managed to provide an application system that can accommodate the development needs for the Cooperatives and Small Business Office as well as Small Business actors in the aspect of data and information processing. As well as providing services to the local community by placing prices and services according to market standards that do not cause distortions in the rural economy caused by BUMDes efforts. With the creation of the UMKM Outlet System innovation in West Java and the IT innovation of Bumdes, Morotai Island Regency managed to provide an application system that can accommodate the development needs for the Cooperatives and Small Business Office as well as Small Business actors in the aspect of data and information processing. As well as providing services to the local community by placing prices and services according to market standards that do not cause distortions in the rural economy caused by BUMDes efforts.